Management of the Implementation of the Arabic Language Learning Program - Sulistiyo, Dwi; Aminudin, Aminudin; Maksum, M. Syukron; Fitri, Yeni Nuriah (Journal of Educational Management Research, 2025)
This study aims to analyse the management of the implementation of the Arabic language learning program. The research focuses on how the actuating function of educational management is applied in planning, organising, and implementing the learning process. Using a qualitative descriptive approach through observation, interviews, and documentation, the study involves two key informants: the head of the Arabic program and an Arabic language teacher. Data analysis follows the Miles and Huberman model through data reduction, presentation, and conclusion drawing. The results show that the Arabic language learning program, initiated in 2020, is conducted daily after the dawn prayer with structured stages—introduction, core activities, and closing—using the thariqah mubasyarah and thariqah ta'bir methods. Learners are grouped into two levels — Ula and Wustho — based on their linguistic abilities, with a focus on four language skills: listening, speaking, reading, and writing. The implementation demonstrates effective management of learning activities despite limitations in teaching staff and learning facilities. This study concludes that Arabic language learning management at Al-Hidayah Batu has been effectively implemented through motivational leadership, adaptive strategies, and the contextual application of educational management principles. The findings provide a practical model for other Islamic boarding schools to improve the quality of Arabic learning through efficient management and pedagogical integration.